How Costly is Energy Conservation? The Energy-GDP Relationship Re-examined for Turkey - Canakci, Mehmet (International Journal of Energy Economics and Policy, 2021)
Economic structure, technology, consumption habits, cultural and similar values vary greatly between countries. Energy consumption included in this structure is theoretically thought to be related to growth output. Could slowing the growth be the cost of reducing energy consumption? In this study, using annual data between 1970 and 2019, it was investigated whether per capita energy consumption affects per capita income asymmetrically or not by using the NARDL model. The feature that makes this study different from similar studies is that it interprets the short and long-term asymmetric effects with the analysis model used and makes a unique contribution to the literature. The findings gave us the conclusion that income is affected in the same way by shocks experienced in energy consumption, and it has been observed that the effect of positive shocks is greater in the long run. However, we conclude that negative shocks are more effective than positive shocks in the short term. Thus, we see that the increase in energy consumption in the long term increases the per capita income, and the decrease in energy consumption has a high as well as negative impact on income per capita in the short term. Based on the fact that the conservation approach is managed in a balanced way, one of the reasons for the slowdown in the national income rates of the countries may be due to the decrease in energy consumption in the long term. Accepting that the conservation approach is managed in a balanced way, one of the reasons for the slowdown in the national income rates of the countries may be due to the decrease in energy consumption in the long term. Keywords: energy consumption, per capita income, economic growth, NARDL asymmetric JEL Classifications: Q43, P44, O47, C12 DOI: https://doi.org/10.32479/ijeep.11428